Accounting as Myth Maker - Kathy Rudkin (Australasian Accounting, Business and Finance Journal, 2007)
Accounting is not only a technical apparatus, but also manifests a societal dimension. This paper proposes that accounting is a protean and complex form of myth making, and as such forms a cohesive tenet in societies. It is argued that there are intrinsic parallels between the theoretical attributes of myth and accounting practice, and that these mythical characteristics sustain the existence and acceptance of accounting and its consequences in societies over time. A theoretical exploration of accounting as a form of myth reveals accounting as pluralistic and culturally sensitive. Such an analysis challenges theoretical explanations of accounting that are presented as a “grand narrative” universal understanding of accounting. Manifestations of the attributes of myth are described in the calculus and artefacts of accounting practice to demonstrate how accounting stories and beliefs are used as a form of myth by individuals to inform and construe their world picture.
Keywords: myth; accounting; society; enlightenment